1996
DOI: 10.1161/01.cir.94.12.3198
|View full text |Cite
|
Sign up to set email alerts
|

Nonsustained Ventricular Tachycardia in Severe Heart Failure

Abstract: In patients with CHF, NSVT is an independent marker for increased overall mortality rate and sudden death. The absence of NSVT and ventricular repetitive beats in a 24-hour Holter indicates a low probability of sudden death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(43 citation statements)
references
References 17 publications
2
39
0
2
Order By: Relevance
“…Next, an important interaction between the presence of a previous MI and NSVT during an acute MI may be present; this may be especially important given the prognostic significance of NSVT in the setting of a healed MI. 19 These issues prompted the current evaluation of the prognostic significance of NSVT in acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…Next, an important interaction between the presence of a previous MI and NSVT during an acute MI may be present; this may be especially important given the prognostic significance of NSVT in the setting of a healed MI. 19 These issues prompted the current evaluation of the prognostic significance of NSVT in acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…30 Nonsustained ventricular tachycardia was associated with SCD in patients with nonischemic cardiomyopathy in the Grupo de Estudio de la Sobrevida en la Insuficiencia Cardiaca en Argentina (GESICA) trial. 31 …”
Section: Ventricular Ectopymentioning
confidence: 99%
“…Few studies have suggested that NSVT are not only an independent marker of total mortality but that they may specifically identify patients at high risk of dying suddenly [11,12]' Despite this, the available evidence would slightly favour the opinion that complex ventricular arrhythmias may be essentially a marker of more advance left ventricular dysfunction and thus may have no significant independent predictive value [13]. This aspect was recently addressed with information from a multicentre Italian data-base, composed of ambulatory patients, including over 1000 patients with available Holter recordings [14].…”
Section: Clinical Rolementioning
confidence: 99%